IPCC expert meeting on the science of alternative metrics, Norway, 18-20 March 2009 meeting Report - Platter,Gian-Kasper (IPCC Working Group I Technical Support Unit, 2009)
Based on the expert contributions and discussions at the Expert Meeting, and taking into account the current status of the science of alternative metrics reported in the scientific literature, the following key conclusions and recommendations to UNFCCC have been formulated in response to the UNFCCC request to IPCC and were unanimously agreed on by meeting participants: 1. Global Warming Potential (GWP) is a well-defined metric based on radiative forcing that continues to be useful in a multi-gas approach. Shortcomings have been identified; however the scientific basis has not been fully established to address these shortcomings comprehensively in any currently discussed metric; 2. The effectiveness of the use of a given metric depends on the primary policy goal, for example to limit the long term temperature change, limit rates of change, avoid particular impacts, and balance costs and benefits. The GWP was not designed with a particular policy goal in mind. Depending on the specific policy goal or goals, alternative metrics may be preferable; 3. The GWP with the time horizon of 100 years is used in the Kyoto Protocol. The numerical value of the GWP can depend markedly on the choice of time horizon. The choice of any particular time horizon involves value judgments in terms of future commitment to radiative forcing; 4. Timely information on potential future policy goals would facilitate research on alternative metrics. Recommendations to the Scoping of IPCC Fifth Assessment Report (AR5): 1. It is important that the assessment of metrics be included in the IPCC AR5 process in an integrated manner with participation from all three working groups and the IPCC Task Force on Greenhouse Gas Inventories (TFI); 2. This process should include an assessment of, and if appropriate, numerical values for metrics that have been proposed in the literature; 3.The assessment should elucidate the relationship between physical metrics and more comprehensive metrics that include economics.(LN).